2023
DOI: 10.3390/microorganisms11092334
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Exosomes Derived from Patients Infected with Non-Tuberculous Mycobacterium and Mycobacterium tuberculosis

Li Wang,
Xubin Zheng,
Jun Ma
et al.

Abstract: The non-tuberculous mycobacterium (NTM) is a very troublesome opportunistic pathogen, placing a heavy burden on public health. The pathogenesis of NTM pulmonary infection is not well-revealed yet, and its diagnosis is always challenging. This study aimed to use a comprehensive proteomics analysis of plasma exosomes to distinguish patients with rapidly growing NTM M. abscessus (MAB), slowly growing NTM M. intracellulare (MAC), and Mycobacterium tuberculosis (MTB). The identified protein components were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These findings indicated the potential of CFL1 as a biomarker of MTB infection. Wang et al investigated plasma exosomes from patients with rapidly growing NTM M. abscessus (MAB), slowly growing NTM M. intracellulare (MAC), and Mycobacterium tuberculosis (MTB) (84). The authors found that the expression of 18 proteins was markedly up-regulated in the plasma exosomes of MAB patients, while the expression of 6 and 10 proteins was up-regulated in MAC and MTB patients, respectively.…”
Section: Proteins In Exosomesmentioning
confidence: 99%
“…These findings indicated the potential of CFL1 as a biomarker of MTB infection. Wang et al investigated plasma exosomes from patients with rapidly growing NTM M. abscessus (MAB), slowly growing NTM M. intracellulare (MAC), and Mycobacterium tuberculosis (MTB) (84). The authors found that the expression of 18 proteins was markedly up-regulated in the plasma exosomes of MAB patients, while the expression of 6 and 10 proteins was up-regulated in MAC and MTB patients, respectively.…”
Section: Proteins In Exosomesmentioning
confidence: 99%